2022
DOI: 10.1101/2022.09.09.507123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of small molecule inhibition of Plasmodium falciparum myosin A informs antimalarial drug design

Abstract: Malaria is responsible for more than a half million deaths per year. The Plasmodium parasites responsible continue to develop resistance to all known agents, despite treatment with different antimalarial combinations. The atypical Myosin A motor (PfMyoA) is part of a core macromolecular complex called the glideosome, essential for Plasmodium parasite mobility and therefore an attractive drug target. Here, we characterize the interaction of a small molecule (KNX-002) with PfMyoA. KNX-002 inhibits PfMyoA ATPase… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The T130A mutation is located distal from the predicted KNX-002 binding pocket [52], suggesting an allosteric mechanism of conferring resistance of the motor to the compound. The T130A mutation is within the transducer subdomain, which plays a critical role in the communication pathway between the nucleotide-binding pocket and the actin-binding domain that is closer to where KNX-002 binds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The T130A mutation is located distal from the predicted KNX-002 binding pocket [52], suggesting an allosteric mechanism of conferring resistance of the motor to the compound. The T130A mutation is within the transducer subdomain, which plays a critical role in the communication pathway between the nucleotide-binding pocket and the actin-binding domain that is closer to where KNX-002 binds.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary SAR data (Figure 3) are consistent with a key role for the pyrazole, cyclopropyl, and p -OMe aryl units within KNX-002, with a generally good correlation between the results of the recombinant myosin ATPase and parasite growth inhibition assays. Subsequent studies, inspired both by our SAR data and the recently reported structure of the PfMyoA-KNX-002 complex [52], should explore the effect on biological activity of: (i) alternative replacements for the thiophene group and (ii) a switch in the positions of the NH and CH 2 groups, amongst other options. Trivedi et al recently reported identification of an analog of KNX-002, named KNX-115, which shows >10-fold improved potency against PfMyoA [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations